A Comprehensive Multi-Dimensional Risk Monitoring Model for Illegal Financial Activities - Zhong-qiang Zhou; Ling Li; Ping Huang (Journal of Risk Analysis and Crisis Response (JRACR))
The rapid expansion of internet finance and fintech has introduced increasingly sophisticated illegal financial activities that challenge traditional regulatory frameworks. Existing regulatory approaches often lack the depth and adaptability to effectively identify and manage these evolving risks. This study proposes a comprehensive, multi-dimensional risk monitoring model tailored to detect illegal financial activities, based on four core dimensions: investor behavior, intermediary platforms, investment products, and regional factors. The model integrates six primary and 26 secondary indicators, enabling quantitative assessment of risk levels and early warning detection. By applying this model to empirical data, our findings highlight specific risk drivers and propose policy recommendations aimed at strengthening regulatory measures. This framework provides regulatory bodies with a practical tool for timely intervention, thereby enhancing financial stability and protecting investor interests.